A deep dive into the capital channel of risk sharing in the euro area - Natalia Martín Fuentes; Alexandra Born; Franziska Bremus; Wieger Kastelein; Claudia Lambert (European Central Bank (ECB), 2023)
This paper investigates the contribution of capital markets to international risk sharing in the euro area over the 2000Q1-2021Q1 period. It provides three main contributions: First, the estimation of country-specific vector autoregressions (VAR) shows that shock absorption through capital markets remains modest, particularly in the southern euro area. Second, we analyse the geographical patterns of the capital channel. While risk sharing between southern and northern euro area countries led the improvements in income smoothing at the beginning of the 2000s, intra-regional capital flows supported income smoothing in the recent past. Third, based on a panel threshold VAR, we analyse how the composition of external capital positions impacts the capital channel. Long-term portfolio debt assets and liabilities as well as equity liabilities significantly improved income smoothing. The effect is more pronounced for northern countries, in line with their larger cross-border portfolios, when compared to the southern countries. Regarding foreign direct investment, only northern countries benefited from inward positions.
Keywords: C23; E62; G11; G15; 330; international risk sharing; capital channel; external financial structure; CMU; panel threshold vector autoregression (TVAR) model